1997
DOI: 10.1007/s004390050391
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of sex chromosomes into sperm nuclei in a man with 47,XXY Klinefelter's karyotype: a FISH analysis

Abstract: Meiotic segregation of the sex chromosomes was analysed in sperm nuclei from a man with Klinefelter's karyotype by three-colour FISH. The X- and Y-specific DNA probes were co-hybridized with a probe specific for chromosome 1, thus allowing diploid and hyperhaploid spermatozoa to be distinguished. A total of 2206 sperm nuclei was examined; 958 cells contained an X chromosome, 1077 a Y chromosome. The ratio of X:Y bearing sperm differed significantly from the expected 1:1 ratio (chi2 = 6.96; 0.001 < P < 0.01). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1
5

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 22 publications
(26 reference statements)
6
37
1
5
Order By: Relevance
“…Preliminary data of FISH analysis on sperm of males with three sex chromosomes shows a small but significant increased frequency of hyperploid sperm as compared to the normal sperm (see for review Gutenbach and others). [17][18][19][20] In this study there were six cases of a structural Y-chromosome aberration (Table 2), an extremely rare occurrence in the normal newborn male population. In four cases we were unable to study the inheritance pattern of the aberration.…”
Section: Sex Chromosomal Aberrations and Their Consequencesmentioning
confidence: 85%
“…Preliminary data of FISH analysis on sperm of males with three sex chromosomes shows a small but significant increased frequency of hyperploid sperm as compared to the normal sperm (see for review Gutenbach and others). [17][18][19][20] In this study there were six cases of a structural Y-chromosome aberration (Table 2), an extremely rare occurrence in the normal newborn male population. In four cases we were unable to study the inheritance pattern of the aberration.…”
Section: Sex Chromosomal Aberrations and Their Consequencesmentioning
confidence: 85%
“…However, it is widely reported that men with KS have higher rates of sex and autosomal aneuploidy [5][6][7][8][9][10][11]. Two approaches on the ability of 47,XXY testes to yield postmeiotic cells exist.…”
Section: Discussionmentioning
confidence: 99%
“…They were reinforced by Egozcue et al [35] who identified the absence of 46,XY spermatogonia in patients negative for spermatids and spermatozoa, and by Mroz et al [36] who showed a clear absence of meiotic competence of 47,XXY cells in mice. Small quantities of studied germ cells such as 20-100 spermatogonia and primary spermatocytes in very few biopsies [1][2][3][4][5]8], as well as technical shortcomings, preclude a definite conclusion [1,4,17,19,20,23] (the study by Yamamoto et al [23] (2002) included 12 biopsies, but lacked information regarding the number of meiotic cells). The CCSS technique, which is based on corresponding size and morphology of the cells and their FISH images, enabled an extended study at three levels:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations